“Recursos tecnológicos para el aprendizaje de la Matemática” - Rocha Angamarca, Lizeth Anabel (2022)
Technology today has taken on great relevance in all areas, and especially in education, for this reason teachers see the need to incorporate ICT in the didactic process, in order to improve student learning, and at the same time that it serves as a support tool, without forgetting that technology is a means and not an end. It is worth mentioning that the subject of mathematics over the years has been considered a difficult discipline to understand. In addition, traditional resources do not respond to the needs of the students of this century, since they focus only on traditional learning. In this same sense, the lack of training in the use and management of educational platforms by educators is added. That is why teachers should focus on the development of digital skills for the development of technological resources, which allow them to achieve mathematical logical reasoning. The objective of this research is to develop technological resources through educational platforms for the learning of mathematics in the students of the sixth grade of basic general education of the "Antonio Nariño" educational unit located in the province of Pichincha, Quito canton, during the academic period 2021 - 2022. The methodology used for the development of this project is part of qualitative research because it allows us to understand reality from the educational institution, in addition, the stages are followed: preparatory, field work, analytical, proposal, and it is of a documentary nature due to the search for information in relation to the study variables, field research was also used for data collection. The method used in this work is the inductive method. The technique used was observation, with its instrument the observation guide that allowed obtaining relevant data from the research subjects. The result is a didactic guide for the development of technological resources in educational platforms for learning mathematics, which contains a wide variety of steps and clear and precise instructions for each educational platform (Kahoot, Khan Academy, Quizizz), from the registration until the elaboration of the resources. This proposal will contribute to the development of d It will focus on the development of digital skills in teachers of the sixth year for the development of technological resources in the subject of mathematics.